Intermolecular sulfenoamination of alkenes with sulfonamides and N-sulfanylsuccinimides to access β-sulfonylamino sulfides and dihydrobenzothiazines. Issue 28 (5th July 2017) - Liu, Tao; Tian, Jun; Gao, Wen-Chao; Chang, Hong-Hong; Liu, Qiang; Li, Xing; Wei, Wen-Long
Abstract : An acid-catalyzed intermolecular sulfenoamination of alkenes is developed with sulfonylamides as the N -source, enabling the synthesis of β-sulfonylamino sulfides and dihydrobenzothiazines. Abstract : An acid-catalyzed intermolecular sulfenoamination reaction of alkenes is developed with sulfonamides as the nitrogen source and N -sulfanylsuccinimides as the sulfur source. This methodology provides a straightforward and general way to synthesize various β-sulfonylamino sulfides with high regio- and diastereoselectivity. The developed method was coupled with intramolecular C–N coupling in a one-pot procedure to afford a series of dihydrobenzothiazine derivatives, a kind of important heterocycle used as biologically active compounds in medicinal chemistry.